Brownian motion and thermophoretic diffusion effects on the dynamics of MHD upper convected maxwell nanofluid flow past a vertical surface. (18th November 2021) - Shah, Nehad Ali; Tosin, Oreyeni; Shah, Rasool; Salah, Bashir; Chung, Jae Dong
Abstract: The suspension of nanoparticles in the base fluid has been tested to improve the heat transfer properties of the fluid since solid metals are characterized with higher thermal conductivity than the convectional working fluid. This present work focuses on the suspension of nanoparticles into the upper convected Maxwell fluid model (UCM) so as to improve the heat transfer efficacy of the fluid. The governing partial differential equations and their related boundary conditions are transformed and parameterized by applying appropriate transformations into a system of non-linear ordinary differential equations and the series solutions are obtained through homotopy analysis method. The impact of various parameters on velocity, temperature and nanoparticles concentration profiles are reviewed and discussed. It is discovered that increasing the Brownian motion increases the thermal conductivity of fluid and hence promotes the effective movement of the nanoparticles.